Do behavioural defence mechanisms explain different levels of trematode infections in congeneric hosts?. Issue 3 (2nd April 2018) - Goellner, S.; Selbach, C.; Friesen, O.C.
Abstract: Susceptibility and tolerance to parasite infection vary greatly between host species. The congeneric isopod species Austridotea annectens and Austridotea lacustris often occur in sympatry and can both serve as intermediate hosts for the trematode Maritrema poulini . However, the intensity and prevalence of infections vary greatly in natural populations, with A. annectens often being heavily infected and A. lacustris rarely being infected. To shed light on the factors that may be involved in infection avoidance in A. lacustris, 100 isopods were collected and experimentally exposed to M. poulini cercariae. To examine for potential behavioural mechanisms, we used carbonated water as a paralysing agent to temporarily stop any movement by the isopods, and exposed paralysed isopods to cercariae. In the experiments, none of the individuals that were exposed to the parasite were found to be infected, although some cercariae seemed to have penetrated isopod hosts. Behavioural defence mechanisms do not seem to explain the different infection levels between A. lacustris and A. annectens, suggesting a physiological, possibly immunological, factor may be present. At the ecosystem level, this suggests a potential dilution effect caused by this low-competency host, and its effects on parasite transmission dynamics should be investigated.